The importance of eco-design in a circular economy with a focus on eco furniture - Trošić, Anamarija (Oeconomica Jadertina, 2021)
In order to decrease the environmental problems in recent years in the world, caused mainly by foreign trade, changes and the introduction of environmental approaches within the business of companies are necessary. Eco design is a powerful tool that pushes boundaries in design, and at the same time participates in raising awareness about environmental protection. At the same time, it reduces environmental pollution and costs, and increases the environmental efficiency and profitability of organizations. Cost reduction can be a particularly important factor in attracting companies to introduce and apply this discipline. It connects with the circular economy and sustainable development and proposes instructions to designers to reduce their negative impact on the environment, choosing environmentally friendly materials, processes and technology. In the world, but also in Croatia, it is necessary to give priority to the development of technology for designing green materials and design technology, design techniques for cleaning paints and compounds and design techniques for a clean environment. The purpose of the article is to provide the public with a deeper understanding of how and whether there is a need to use more green products and furniture. Businesses need to focus on marketing sustainable furniture to a greater extent in order to increase the purchase, but also the awareness of green furniture consumption. The furniture industry is one of those committed to improving its operations in the territory of environmental protection. Eco furniture is easily repaired, disassembled and recycled, and there is awareness in its design, production and end use. Era grupa d.o.o. is a company that deals with ecological furniture that was designed and manufactured in Croatia and has reached a level of high environmental and ethical awareness. The aim is to produce an impact on the qualitative improvement of products in the furniture industry, which is based on the use of ecodesign at all stages of production and reduction of emissions of harmful substances and respect for the health and safety of workers and end users. Also, their desire is to establish a Croatian eco-design that is recognizable and that will affect the competitiveness of Croatian products in the world.